Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4103/1673-5374.253511
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for peripheral nerve injury: decellularized nerve conduits and Schwann cell transplantation

Abstract: In recent years, the use of Schwann cell transplantation to repair peripheral nerve injury has attracted much attention. Animal-based studies show that the transplantation of Schwann cells in combination with nerve scaffolds promotes the repair of injured peripheral nerves. Autologous Schwann cell transplantation in humans has been reported recently. This article reviews current methods for removing the extracellular matrix and analyzes its composition and function. The development and secretory products of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…Following a PNI, the damaged nerve can be regenerated through nerve end-to-end anastomosis, autologous nerve transplantation, or nerve conduits ( Kubiak et al, 2020 ). However, the nerve regeneration outcomes of these treatments, and especially the recovery of nerve function, are not always favorable, with painful neuroma, anastomotic scars, and flawed development of motor sensory nerve axons being commonly reported ( Sullivan et al, 2016 ; Han et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following a PNI, the damaged nerve can be regenerated through nerve end-to-end anastomosis, autologous nerve transplantation, or nerve conduits ( Kubiak et al, 2020 ). However, the nerve regeneration outcomes of these treatments, and especially the recovery of nerve function, are not always favorable, with painful neuroma, anastomotic scars, and flawed development of motor sensory nerve axons being commonly reported ( Sullivan et al, 2016 ; Han et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Schwann cell transplantation enhances myelination and spinal nerve regeneration in the spinal cord [ 300 - 304 ]. Schwann cell grafts could also be a potential therapy for peripheral nerve injury [ 305 ]: SC transplantation successfully enhances sciatic nerve regeneration not only in rodents [ 302 , 306 - 310 ], but also in monkeys [ 311 ] and in humans [ 312 ]. However, SC therapy presents the obstacle of limited cell sources.…”
Section: Discussionmentioning
confidence: 99%
“…Many preclinical studies have shown that SCs obtained via in vitro culture methods form a bridge across a lesion site, recruit endogenous SCs, promote axon growth and sparing, and provide a new myelin sheath to regenerated and demyelinated axons in the PNS [16,120,121] and CNS [10,14,118]. SCs do not naturally reside in the CNS but cells with SC characteristics can be found within traumatic and demyelinating lesions in the brain and the spinal cord [122].…”
Section: Cell Therapymentioning
confidence: 99%
“…For instance, SCs can be isolated from assorted mouse models [13] and transgenic animals expressing gene reporters. In this way, researchers have been able to compare cell behavior in vitro and in vivo, and trace the fate of transplanted SCs to grasp the associated mechanisms of repair, migration and myelination in central and peripheral nerve lesions [10,[14][15][16]. A particular advantage of SCs is that it is possible to manufacture them at a large scale from human autologous tissues following guidelines compatible with safe manufacturing practices, which has made it possible to re-implant cultured SCs for therapeutic benefit in human patients [17].…”
Section: Introductionmentioning
confidence: 99%